The role of the insulin-like factor of growth 1 in the development of the processes of myocardial remodeling in women with arterial hypertension and metabolic syndrome - N. E Zakirova; I. E Nikolaeva; A. N Zakirova; E. G Nurtdinova; E. Z Galiyeva; D. F Nizamova (КардиоСоматика, 2018)
Aim: to establish the role of insulin-growth factor (IGF)-1 in myocardial remodeling in female patients with arterial hypertension (AH) and metabolic syndrome (MS) and different stages of obesity Materials and methods. The study included 108 women with AH and MS, divided into 3 groups according to stage of obesity, and 28 healthy women. It was assessed the concentration of IGF-1, status of hemodynamic and types of left ventricle's remodeling. Results. Concentric remodeling and IGF-1 elevation prevailed in patients with AH and first stage of obesity. Concentric hypertrophy of left ventricle and normal level of IGF-1 were established in patients with second stage of obesity. Lack of IGF-1 were determined in women with obesity 3rd stage and eccentric hypertrophy. Correlation analysis in patients with 2-3 stages of obesity showed the linkages between concentration of IGF-1 and hemodynamic parameters. Conclusion. The level of concentration of IGF-1 in patients with AH and MS correlates with remodeling types and stage of obesity.